Samson in the snow - Stead, Philip Christian (New York : Roaring Brook Press, 2016)
When friendly giant mammoth Samson falls asleep and wakes up in the middle of a blizzard, he finds and shelters a little red bird and a flower-loving mouse, beginning new friendships for all.
"A Neal Porter Book."
Keywords: Mammoths -- Juvenile fiction; Friendship -- Juvenile fiction; Snow -- Juvenile fiction; Animals -- Juvenile fiction; Picture books; Mammoths -- Fiction; Friendship -- Fiction; Snow -- Fiction; Animals -- Fiction; Snow -- Juvenile fiction; Animals; Picture books; Mammoths; JUVENILE FICTION -- Animals -- Dinosaurs & Prehistoric Creatures; JUVENILE FICTION -- Social Issues -- Friendship; JUVENILE FICTION -- Animals -- Birds; Friendship; Snow; Fiction; Juvenile works